Contact and loss: Spanish and Indigenous languages in the Río de la Plata between the 16th and the 19th century - Bertolotti, Virginia; Coll, Magdalena (Boletín de Filología, 2013)
This paper analyzes the historical linguistic contact between indigenous languages and Spanish in the current territory of Uruguay as well as the reasons for its outcome, namely the displacement and loss of autochthonous languages in the Río de la Plata. The study proposes two stages to describe the history of language contact between the Spaniards and the indigenous peoples: while the first one (16th century) is characterized by the initial encounters between both, the second one (17th and 18th century) is characterized by European settlement and colonization, which led to the linguistic acculturation of the Indigenous peoples in the 19th century. The loss of indigenous languages is explained by four types of circumstances: sociodemographic, ethnolinguistic, cultural-historical, and technological circumstances. In particular, the characterization of the latter provides an original insight into the appropriation of writing as one of the factors which favored the shift from indigenous languages to Spanish.